DISASTER MITIGATION AS AN EFFORT TO MINIMIZE THE IMPACT OF FLOODS IN LAMONGAN DISTRICT - Nur Aisyah Lusiana; Agus Widiyarta (DIA: Jurnal Administrasi Publik, 2021)
Flood is one of the most dominant disasters in Indonesia with an incident that tends to increase. Lamongan District is an area with a fairly high risk of flooding due to the intensity of which it occurs every year. The high risk of flooding is caused by two reasons, the Bengawan Solo flow and the rainfall (the Bengawan Njero flow). Every flood disaster that occurs will certainly cause various impacts from damage to infrastructure, loss of property, and casualties. Disaster management efforts are certainly carried out to minimize the risk and impact of flood disasters in Lamongan District, such as through disaster mitigation. This research aims to determine disaster mitigation carried out in Lamongan District as an effort to minimize the impact of flooding. This research used descriptive qualitative research methods. Disaster mitigation in this research is divided into two according to Perka BNPB Number 4 of 2008, active disaster mitigation and passive disaster mitigation. The results of this research indicated that active mitigation in Lamongan District was carried out through, making flood disaster signs, supervising spatial planning, conducting training and counseling on flood disasters to officials, communities, and students, planning evacuation places and flood disaster evacuation routes and making embankment reinforcement. Meanwhile, passive mitigation in Lamongan District was carried out through, drafting laws and regulations, making flood-prone maps, making guidelines for every disaster management activity, making disaster posters, conducting flood risk studies, conducting disaster education, forming village forums, and prioritizing disaster management in development planning.